Analisis Standar Tugas Akhir Dkv dengan Kebutuhan Industri Kreatif - Made Aditya Abhi Ganika; Zulfi Hendri; Rony Siswo Setiaji (Attractive : Innovative Education Journal, 2024)
Analysis of Final Project Standards in Visual Communication Design (VCD) in Relation to the Needs of the Creative Industry for Preparing Professional Teachers. This research aims to explore the Final Project of students, which is one of the mandatory requirements that must be fulfilled before students can be declared graduated by a Higher Education institution. In the Fine Arts Education study program, there is still no standard for the final project, especially for students who take topics related to Visual Communication Design (VCD). The final project should have a standard to produce professional graduates. This standard will later serve as a guideline that facilitates students in the process of creating a design product. The aim of this research is to describe the types of Final Project topics chosen by VCD students, describe the standards of VCD students' Final Projects based on the topics, and describe the evaluation and assessment process of the VCD students' Final Projects. The methodology used is descriptive qualitative, utilizing literature studies and Focus Group Discussions (FGD). The FGD was conducted with experts and practitioners to formulate the standard for VCD students' Final Projects.